Diversification Impact on Financial Performance through Capital Structure - Hamdat, Aminuddin; Nurdin, Maryam; Taufiq HB, Muh. Imam; Yendra, Yendra (Jurnal Manajemen Bisnis, 2026)
This research aimed to analyze the influence of diversification strategies on corporate financial performance, with capital structure serving as an intervening variable. The study focused on manufacturing companies in the basic chemical industry sector listed on the Indonesia Stock Exchange (IDX) during 2021–2022. A quantitative approach was employed, using Panel Data Regression and Path Analysis, both processed in EViews. Purposive sampling was used, yielding 30 companies as units of analysis over two years, for a total of 60 observations. Model specification tests, specifically the Chow and Hausman tests, confirmed that the Fixed Effect Model (FEM) was the most appropriate estimation method for this study. The results revealed that diversification strategies, proxied by the Herfindahl Index (HI), had a significant positive direct effect on financial performance (ROA). However, diversification strategies did not significantly affect capital structure (DAR and DER), and capital structure did not mediate the relationship between diversification and financial performance. These findings indicate that external financing levels do not drive improvements in financial performance through diversification; rather, they are determined by internal management efficiency and strategic resource utilization. The practical implication is that company management needs to prioritize diversification as an effective growth strategy by optimizing internal capabilities rather than relying on adjustments to the financing structure.